SASTRA BANDING NOVEL KEMARAU KARYA A.A NAVIS DENGAN NOVEL THE DRY KARYA JANE HARPER - Nitami, Adya; Hartati, Dian (Universitas Hamzanwadi, 2022)
The purpose of this study is to compare literary works in the novel Kemarau by A.A Navis and the novel The dry by Jane Harper. The method used in this research is descriptive qualitative research method. In the management of the data generated using the analysis of the theory of sociology of literature. This study uses a comparison table contained in the novel Kemarau by A.A Navis and the novel The Dry by Jane Harper. The results of comparison of social values contained in the two novels, the novel Kemarau by A.A Navis explains social values and the values about life contained in the novel Kemarau by A.A Navis. Meanwhile, Jane Harper's novel The Dry is quite the opposite, but there are still moral values inserted. Through this research, it is hoped that it can increase reader's interest in literary works, and can increase the interest of researchers in comparative literary research.Keywords: Novel, Comparative Literature, Drought, Fiction.